2015
DOI: 10.2215/cjn.11541114
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Disciplinary Biomarkers Research

Abstract: Significant advances are needed to improve the diagnosis, prognosis, and management of persons with CKD. Discovery of new biomarkers and improvements in currently available biomarkers for CKD hold great promise to achieve these necessary advances. Interest in identification and evaluation of biomarkers for CKD has increased substantially over the past decade. In 2009, the National Institute of Diabetes and Digestive and Kidney Diseases established the CKD Biomarkers Consortium (http://www.ckdbiomarkersconsorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Some of the challenges of this workflow have been noted in recent consortium and meeting statements. 81,82 Biomarkers should be validated in >1 well-characterized sample set before application in a large-scale study. An important facet of assay development is attention to the use of appropriate control samples.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…Some of the challenges of this workflow have been noted in recent consortium and meeting statements. 81,82 Biomarkers should be validated in >1 well-characterized sample set before application in a large-scale study. An important facet of assay development is attention to the use of appropriate control samples.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…The request for applications proposed 'Discovery of new biomarkers in body fluids (serum, urine, saliva, tears) or tissues from well-characterized patients with stable or progressive CKD and appropriate controls using genomic, proteomic or metabolomic techniques, to assess structure, function, injury, repair, and progression of chronic kidney damage.' The CKD BioCon entered the field of biomarker discovery with considerable assets that included access to 58,000 specimens, multidisciplinary expertise in nephrology, proteomics, clinical chemistry, epidemiology, and informatics [17]. To date, several studies have been performed by the CKD BioCon both examining previously identified biomarker candidates and performing proteomic-based discovery.…”
Section: Difficult Lessons Learnedmentioning
confidence: 99%
“…Despite a surfeit of negative findings by the CKD BioCon consortium, a number of valuable lessons have been learned as to the structure of renal biomarker studies for proteomic analysis and development of new mass spectrometry-based assays. These include the proper collection, processing and storage of specimens from large cohorts for proteomic analysis, development of standard operating procedures for multiple reaction monitoring, external quality control for assays including blind duplicates, and proficiency samples from quality control pools [17]. Substantial progress has been made in developing multiple reaction monitoring assays in urine, particularly of the candidate CKD biomarker uromodulin [22,23].…”
Section: Difficult Lessons Learnedmentioning
confidence: 99%
“…Collection and storage of blood for subsequent biomarker measurement may contribute to the understanding of disease pathogenesis (26), and in a large RCT the incremental cost of collecting patient samples is relatively low. Because of the long duration of trials (EVOLVE started in August 2006 and finished in January 2012, with primary publication of trial results in November 2012) and the potential for biomarker research to be published during the execution of the trial, we did not designate which biomarkers would be measured until after the trial was completed.…”
Section: Biomarkersmentioning
confidence: 99%